PENGARUH PENYAJIAN LAPORAN KEUANGAN DESA, PENGENDALIAN INTERNAL, DAN MORALITAS INDIVIDU, TERHADAP PENCEGAHAN FRAUD YANG TERJADI DALAM PENGELOLAAN ALOKASI DANA DESA - Rani Sembiring (SUAN PUBLISHER, 2024)
This study aims to determine and analyze the Effect of Presentation of Village Financial Statements, Internal Controls and Individual Morality on Fraud Prevention That Occurs in the Management of Village Fund Allocations (Case Study of Desa Aman Damai, Kec. Sirapit, Kab. Langkat). This research is a quantitative research, namely by presenting the research results in the form of numbers which are then explained and interpreted in a description in order to test the hypothesis. The population in this study were all village officials and the Village Consultative Body totaling 40 people and the sampling method used the method probability sampling where all the population is selected as a sample. The data used in this study is primary data obtained from respondents who filled out the questionnaire